The effect of organic, chemical and hybrid fertilizers on plant development and antioxidant level in hydroponic pak choy (Brassica rapa L. var. chinensis) - Lizar, Nor Hasni (2019)
Climate change, food security and over dependency of cheap food import are one of the major concerns facing this country. It is clear that Malaysia needs to focus more on food crops toward self-sufficiency by providing more agricultural commodities, protections and incentives towards local farmers. Therefore, to overcome these problems a study was initiated to study the impact of organic, chemical and hybrid fertilizers on NPK content, plant growth, chlorophyll and Brix content, and the antioxidant level of pak choy (Brassica rapa var. chinensis) in a hydroponic farming. Treatments of different types of fertilizer composed of: 100% chemical, 100% organic and hybrid (50% chemical + 50% organic) were used for this study. The planting experiment was conducted in completely randomized design with eighteen replications under rain sheltered area near the Department of Biology. The plant growth, chlorophyll and Brix content, and the antioxidant level were measured following established methods. There were significant different of NPK content of all types of fertilizer. Organic fertilizer has the highest N content, but the plant height & leaf area data showed poor plant development. Hybrid fertilizer showed no significant different in plant growth with chemical fertilizer. Plant treated with hybrid fertilizer had the highest Brix content with an average of 6.17±0.76. Chemical, organic and hybrid fertilizer showed no significant different to the amount of chlorophyll a, b & carotenoid. The phenolics content of the pak choy treated with organic fertilizer was significantly different between pak choy treated with hybrid fertilizer only (p<0.05). Pak choy planted in hybrid fertilizer recorded highest antioxidant activity (9.69±0.35mg/ml) compared to organic and chemical fertilizer by denoting low concentration of IC50 (p<0.05). In terms of scoring method, pak choy treated in hybrid fertilizer has the highest value suggesting that these plants have balance amount (in term of quantity and quality) of all beneficial aspect studied in this research. In conclusion, the results indicated that application of hybrid fertilizer produced better plant growth performance, productivity and as good as chemical fertilizer therefore minimizing the use of chemical fertilizer.